Demystifying augmentative and alternative communication - Fernandes, Ana Matos (2024)
Thus, this paper aims to clarify myths/wrong or less clear ideas about AAC, based on bibliographic research (used as a data collection technique) carried out as part of the Communication Disorders Curriculum Unit of the Master's Degree in Special and Inclusive Education at the School of Education of the Polytechnic Institute of Bragança - Portugal. By challenging these myths, we hope to promote a broader understanding and acceptance of AAC, enabling individuals with communication difficulties to reach their full communicative potential and actively participate in society. In this sense, based on scientific evidence from literature research, it is possible to debunk around nine myths or misconceptions addressing issues such as the impact on natural speech, the suitability of AAC for individuals with severe disabilities, the need for prior skills and the appropriate age for implementation. Each myth is deconstructed based on scientific evidence and practical experience, highlighting the benefits and effectiveness of AAC in various situations. Finally, conclusions are presented that highlight the importance of challenging these myths and promoting a broader understanding of AAC, with a view to creating more inclusive and empowering environments for all individuals, regardless of their communication skills or limitations.